The development finance challenges facing Latin America in the 1990s - Jürgen Westphalen (Intereconomics, 1991)
Growth in Latin America in the 1980s was much slower than it had been in previous decades and real resource transfer has been negative since 1983. What are the chances that this situation will change in the nineties? Where can the necessary development finance come from? Can bottlenecks be avoided?
Keywords: 330; Latin America